2015
DOI: 10.1093/ecco-jcc/jjv238
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is Associated With Extra-intestinal Manifestations in Inflammatory Bowel Disease

Abstract: There is a robust dose-dependent association between active smoking and EIMs in both CD and UC patients. Smoking cessation was found to result in a rapid reduction of EIM prevalence to levels encountered in never smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 42 publications
2
41
0
Order By: Relevance
“…13 Smoking has also been associated with the presence or development of extraintestinal manifestations in IBD, with arthralgias being 1 of the most common. 14 In our cohort we observed active smokers to be at a 3-fold increased risk for infections with VDZ, and the only noninfectious adverse event reported in active smokers was arthralgia. Given respiratory tract infections and arthralgias were 2 of the most common adverse events observed, this highlights the importance of counseling active smokers on smoking cessation when starting VDZ to optimize the safety profile.…”
Section: Discussionmentioning
confidence: 49%
“…13 Smoking has also been associated with the presence or development of extraintestinal manifestations in IBD, with arthralgias being 1 of the most common. 14 In our cohort we observed active smokers to be at a 3-fold increased risk for infections with VDZ, and the only noninfectious adverse event reported in active smokers was arthralgia. Given respiratory tract infections and arthralgias were 2 of the most common adverse events observed, this highlights the importance of counseling active smokers on smoking cessation when starting VDZ to optimize the safety profile.…”
Section: Discussionmentioning
confidence: 49%
“…Nonetheless, in a cross-sectional analysis of three IBD cohort studies, smoking has been identified as an independent risk factor for EIM in both CD and UC. 111 Of note, this association between smoking and EIM was dose-dependent. 111 Furthermore, smoking cessation was associated with a reduction of EIM prevalence.…”
Section: Environmental Factorsmentioning
confidence: 93%
“…111 Of note, this association between smoking and EIM was dose-dependent. 111 Furthermore, smoking cessation was associated with a reduction of EIM prevalence. 111 Both findings make the results more reliable.…”
Section: Environmental Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies didn't prove sex as risk factor [12,14]. Correlation between smoking and rheumatic manifestations of IBD had been discussed with contradictory results [15]. The impact of intestinal disease on risk for AS showed different conclusions.…”
Section: Authorsmentioning
confidence: 99%